(untitled) (GIST – Education and Learning Research Journal, 2022)
This paper analyzes a few significant differences between Spanish and English in relation to phonological patterns. First, a short introduction is given about these two languages, and it is briefly explained in what linguistic aspects they are similar or different. Then, each of these linguistic features is analyzed in detail, clearly establishing the differences existing between Spanish and English. The specific phonological features that are addressed on this academic paper are vowel and consonant phonemes, diphthongs and triphthongs, as well as syllable and sentence stress. Furthermore, several pronunciation difficulties for Spanish speakers are discussed. Finally, some didactic implications are considered so that teachers can help their students of either language learn the second one considering important linguistic features.